Testicular Cancer: New Insights on the Origin, Genetics, Treatment, Fertility, General Health, Quality of Life and Sexual Function - Garolla, Andrea; De Giorgi, Ugo; Milardi, Domenico (Frontiers Media SA, 2020)
Testicular cancer (TC) is the most frequent solid malignancy in young men aged between 15 and 40 years. The worldwide incidence is about 7.5 per 100,000 subjects, but the rates vary considerably between countries and ethnic groups. About 95% of all TCs are represented by testicular germ cell tumors (TGCTs), which include seminoma and non-seminoma histological types. It has been reported that about 18,000 European subjects over reproductive age develop a TGCT every year and its incidence is increasing in several countries over the past 50 years. Early diagnosis and modern treatment have resulted in over 95% survival rate and improved quality of life in testicular cancer survivors. However, the benefits of cancer treatments may hide some risks. In fact, possible side effects can be developed during the treatment itself or later from months to years after the completion of therapy, persisting during the whole life. Therefore, TGCT survivors frequently complain a number of healthy problems such as infertility, hypogonadism, metabolic syndrome, osteoporosis, sexual disorders, depressed mood, and in general impaired quality of life. This aspect is the most serious and potentially life threatening effect in TGCT survivors. Many risk factors have been studied as a pre-disposing factor in the development of this cancer, but only for some there is a high level of evidence. In recent times, progressive increases in the incidence of male reproductive disorders inclusive of hypospadias, cryptorchidism, poor semen quality, and testicular cancer, suggested a common foetal origin. The central hypothesis of this observation asserted that these disorders may all collectively signify testicular dysgenesis syndrome (TDS). It is generally assumed that the development of TGCT is under endocrine control. In particular, unbalanced androgen/estrogen levels and/or activity during embryogenesis, are believed to represent the key events for TGCT development and progression. Furthermore, recent evidence has suggested genetic association of TGCT with variations in genes involved in hypothalamic-pituitary-testicular axis and steroidogenic enzymes. Therefore, hormonal carcinogenesis is an important and controversial area of current research in TGCT, and further attention is given to endocrine environment influencing testicular development during foetal life. The objective of this Research Topic is to group a collection of articles focused on new and more recent insights about TGCT.